Controlling the microstructure of resorcinol–furfural aerogels and derived carbon aerogels via the salt templating approach. Issue 11 (18th February 2019) - Zhang, Haiming; Feng, Junzong; Li, Liangjun; Jiang, Yonggang; Feng, Jian
Abstract : The control strategy for the microstructure of resorcinol–furfural (RF) aerogels and derived carbon aerogels is attracting attention in different applications such as adsorbents, electrochemical electrodes, thermal insulation and so on. Abstract : The control strategy for the microstructure of resorcinol–furfural (RF) aerogels and derived carbon aerogels is attracting attention in different applications such as adsorbents, electrochemical electrodes, thermal insulation and so on. In this work, RF aerogels with abundant micropores were synthesized successfully by the sol–gel process using resorcinol (R) and furfural (F) as monomers, methanol (M) as the solvent, hexamethylenetetramine (H) as the catalyst, and zinc chloride (Z) as a salt template. The RF aerogels with micro specific surface area up to 228.28 m 2 g −1 thus obtained have a high specific surface area (547.96 m 2 g −1 ), and have a large total pore volume (0.7960 cm 3 g −1 ). The carbon aerogels were synthesized by pyrolyzing RF aerogels under a flowing argon atmosphere. Compared with carbon aerogel synthesized without a salt template, carbon aerogels synthesized with a salt template have higher BET specific surface area and larger total pore volume. Moreover, the mean pore size and particle size of carbon aerogels could be greatly reduced by adding the salt template. The influence of M/R ratio (molar ratio of methanol to resorcinol) and Z/R ratio (molar ratio of zinc chloride to resorcinol) on the microstructure of RF aerogels was systematically investigated. The salt templating is an effective approach for controlling the microstructure of RF aerogels and derived carbon aerogels.